COPPER ANO PROTEIN IN THE HEMOLYMPH OF THE SPINY LOBSTERS (CRUSTACEA: PALINURIDAE) - Bastos, José Raimundo; Bezerra, Roberto Cláudio F. (Arquivos de Ciências do Mar, 2018)
The objective of this paper isto determine the average quantity of copper and protein in the hemolymph of spiny lobsters Panulirus argus (Latreille) and Panulirus laevicauda (Latreille), with the aim of making a comparison with other species studied, as well as verifying the importance of the simple correlation between total length of the animais and the quantity of copper and protein in the hemolymph.